Sobrevivência de Dalbulus maidis em plantas hospedeiras alternativas na entressafra de milho - Arcangeli, Geovana Alves (2023)
Corn plays a fundamental role in Brazil and globally, being an essential crop for both human and animal nutrition. Furthermore, it serves as an essential raw material for the production of a variety of products, including beverages, fuels, polymers and others. However, several factors can influence corn productivity, such as soil, climate, cultivar, cultural practices and management of pests, diseases and weeds. This scenario becomes even more challenging with the second harvest or 'safrinha' which can contribute to the permanence of hosts in favorable conditions in the field, this can provide a greater incidence of pests and/or diseases caused by insect vectors, such as Dalbulus maidis (corn leafhopper). Studies regarding the survival capacity of the corn leafhopper on alternative host plant species, that is, species that can serve as shelter and/or food during the off-season, are still scarce. In this context, it is essential to identify possible host plants and determine insect vector management to minimize losses attributed to the corn leafhopper. The objective of this work was to evaluate the survival and development of corn leafhoppers on plants. Weed species were selected because they have a similar botanical classification to corn or due to their common occurrence in corn fields. For survival tests, two tests were carried out: on groups of plants and on individual plants, where the survival, oviposition and “bridge” of insects were evaluated. Survival assessments were carried out daily after the leafhoppers were confined in cages until all insects died. Oviposition assessments were carried out seven days after infestation. To do this, the leaves were detached from the plants and cut into smaller sizes to count the eggs using a stereoscopic microscope. The existence of several species of weeds can provide refuge and food, prolonging longevity, at least for a part of the leafhopper population. It is likely that, in agricultural environments, these weeds play a role in harboring populations of migrating leafhoppers from recently harvested corn fields, thus ensuring the survival of some of these insects until the emergence of new seedlings in the area. However, it is a fact that corn plants play a very important role in the survival of Dalbulus maidis in crops, and the presence of volunteer corn plants, staggered, late and continuous plantings can play a fundamental role in the population increase observed in recent harvests. Considering the data obtained, weeds are of marginal importance in maintaining Dalbulus maidis populations.